Socio-economic consequences of cattle predation by the Endangered Persian leopard Panthera pardus saxicolor in a Caucasian conflict hotspot, northern Iran - Babrgir, S; Farhadinia, M; Moqanaki, E (Cambridge University Press, 2015)
In the Caucasus the Endangered Persian leopard Panthera pardus saxicolor has been persecuted to the verge of extinction, primarily as a result of conflict with people over livestock predation. The socio-economic factors that influence this interaction have received little attention and the attitudes of local people towards leopards remain unknown. Here we assess the extent of cattle predation by leopards and how this influences people's attitudes towards leopards among village residents around the Dorfak No-Hunting Area, a priority reserve in the Iranian Caucasus. In a survey of 66 households, 48% of interviewees reported losing cattle to leopards during 2009–2011. A mean of c. 0.7 head of cattle per interviewed household was reportedly killed by leopards over the 3-year survey period. Cattle predation peaked during warm seasons, when most family members were busy with rice farming-related activities, thus leaving their cattle grazing unguarded in the forest. Regardless of the intensity of cattle predation or socio-economic status, 80% of respondents perceived leopards as a pest, with 45% of interviewees expressing support for either licensed hunting or culling of the Dorfak leopards. We recommend that the Iranian government considers the financial consequences of livestock loss for poor rural communities across the leopard's range. In addition, a combination of different livestock husbandry practices, with the direct involvement of local residents, is essential to ensure the long-term survival of the regional leopard population of the Caucasus.